An experimental translocation identifies habitat features that buffer camouflage mismatch in snowshoe hares - Wilson, Evan C.; Shipley, Amy A.; Zuckerberg, Benjamin; Peery, M. Zachariah; Pauli, Jonathan N. (Conservation letters, 2019)
Conservation for species impacted by climate change often occurs at scales impractical for local land managers. Snowshoe hares (Lepus americanus) are one of the most well‐documented species declining from climate change–specifically a reduction in snowcover–yet clear management strategies have yet to emerge. To test whether camouflage mismatch is reducing hare survival we translocated 96 hares to a site recently extirpated of snowshoe hares, and monitored coat color change, mismatch with snow, habitat use, and weekly survival in winter‐spring of 2017. Hare survival was low during periods of camouflage mismatch, and mismatched hares were 3.2 × less likely to survive, but this pattern varied by habitat. We found that aspen‐alder stands >5 hectares negated the mortality costs of mismatch. We provide experimental evidence that mismatch is driving the range contraction of snowshoe hares, and identify specific habitats to buffer the consequences of climate change on this declining winter specialist.